Globalisation and the future of the welfare state - Yu-Fu Chen; Holger Görg; Dennis Görlich; Hassan Molana; Catia Montagna; Yama Temouri (WWWforEurope, 2014)
The conventional wisdom is that increasing globalisation requires a reduction in the provision of the welfare state among industrialised countries as the distortions resulting from this type of expenditure undermine international competitiveness and the ability of countries to attract and/or retain industries. However, there are empirical observations and theoretical models that are not in line with this conventional wisdom – see for instance Molana and Montagna (2006) and Goerg, Molana and Montagna (2009). We will carry out an empirical study using multi-country data for selected OECD countries to investigate the link between two aspects of globalisation, namely international competitiveness and foreign direct investment, and the size of government expenditure on social policies. The paper will also take into account theoretical arguments and empirical evidence from related studies.
Keywords: F15; H11; H50; 330; Challenges for welfare system; Globalisation; Welfare state